2013
DOI: 10.5333/kgfs.2013.33.3.171
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Chemical Composition of Fresh Whole Crop Barley Silages by Near Infrared Spectroscopy

Abstract: Near infrared reflectance spectroscopy (NIRS) has become increasingly used as a rapid and accurate method of evaluating some chemical compositions in forages and feedstuff. This study was carried out to explore the accuracy of near infrared spectroscopy (NIRS) for the prediction of chemical parameters of fresh whole crop barley silages. A representative population of 284 fresh whole crop barley silages was used as a database for studying the possibilities of NIRS to predict chemical composition. Samples of sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
2
5
0
1
Order By: Relevance
“…The chemical compositions of the fresh barley forages and of silages ensiled for 100 days are similar to those reported in previous studies using the same hybrids (Lee et al 2014;Kim et al 2015). Park et al (2008) reported higher concentrations of DM and CP in their fresh forages relative to those of the hybrids in this study, presumably reflecting differences in soil type, fertilization and maturity at harvest. For unknown reasons, the CP concentration was reduced by inoculation after 100 days of ensiling.…”
Section: Chemical Composition Of Fresh Forages and Silages Of 100 Dayssupporting
confidence: 88%
See 2 more Smart Citations
“…The chemical compositions of the fresh barley forages and of silages ensiled for 100 days are similar to those reported in previous studies using the same hybrids (Lee et al 2014;Kim et al 2015). Park et al (2008) reported higher concentrations of DM and CP in their fresh forages relative to those of the hybrids in this study, presumably reflecting differences in soil type, fertilization and maturity at harvest. For unknown reasons, the CP concentration was reduced by inoculation after 100 days of ensiling.…”
Section: Chemical Composition Of Fresh Forages and Silages Of 100 Dayssupporting
confidence: 88%
“…Two barley hybrids used in this study were developed at National Institute of Crop Science, RDA, Suwon, South Korea by the conventional crossbreeding method (Park et al 2008). Yuyeon (Fig.…”
Section: Materials and Methods Forage Production And Silagementioning
confidence: 99%
See 1 more Smart Citation
“…The statistics of the calibrations with the lowest SECV on the whole data set and those of the corresponding calibrations on the calibration set are given in The moisture content of silage is very important in the forage quality control and feeding system. The standard error of cross validation (SECV) for the prediction of moisture content in winter rye silage sample (1.51%) was similar to those reported by Park et al (2013; and Sinnaeve et al (1994).…”
Section: Predicting Chemical Parameters Of Winter Rye Silagesupporting
confidence: 78%
“…Un trabajo realizado con un colectivo similar al de este trabajo, una colección de 50 muestras secas y molidas de ensilados experimentales de girasol, cuyo resultado mostró una menor capacidad predictiva para la estimación del pH que en el presente trabajo, con valores inferiores de r 2 vc (0.86), RER (5.9), RPD (2.5) y mayor de EEVC (0.44) (22) . En otros trabajos, sobre muestras en estado fresco, han obtenido una menor capacidad predictiva para el valor de pH que en este trabajo, con valores de r 2 vc de 0.85, 0.72 y 0.78 en ensilados de hierba (4) , ensilados de cebada (23) y ensilados de raigrás (24) , respectivamente.…”
Section: Introductionunclassified